Equality of Opportunities and Balance of Interests - Harutyunyan, Edvard (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
In liberal democratic societies the Market and the State are two irreplaceable structures, which organize and regulate daily production of stability of social life. If market economy and free competition form the domain of “equality of opportunities”, the state is the guarantor of “balance of interests”. Proceeding from these functions of the Market and the State, the principle of division of economic and political powers is viewed as a precondition for constructing social-economic life on the bases of justice and equality.